Cognitive impairments associated with alterations in synaptic proteins induced by the genetic loss of adenosine A2A receptors in mice. (November 2017) - Moscoso-Castro, Maria; López-Cano, Marc; Gracia-Rubio, Irene; Ciruela, Francisco; Valverde, Olga
Abstract: The study of psychiatric disorders usually focuses on emotional symptoms assessment. However, cognitive deficiencies frequently constitute the core symptoms, are often poorly controlled and handicap individual's quality of life. Adenosine receptors, through the control of both dopamine and glutamate systems, have been implicated in the pathophysiology of several psychiatric disorders such as schizophrenia and attention deficit/hyperactivity disorder. Indeed, clinical data indicate that poorly responsive schizophrenia patients treated with adenosine adjuvants show improved treatment outcomes. The A2A adenosine receptor subtype (A2A R) is highly expressed in brain areas controlling cognition and motivational responses including the striatum, hippocampus and cerebral cortex. Accordingly, we study the role of A2A R in the regulation of cognitive processes based on a complete cognitive behavioural analysis coupled with the assessment of neurogenesis and sub-synaptic protein expression in adult and middle-aged A2A R constitutional knockout mice and wild-type littermates. Our results show overall cognitive impairments in A2A R knockout mice associated with a decrease in new-born hippocampal neuron proliferation and concomitant changes in synaptic protein expression, in both the prefrontal cortex and the hippocampus. These results suggest a deficient adenosine signalling in cognitive processes, thus providing new opportunities for the therapeutic management of cognitive deficits associated with psychiatric disorders. Highlights: Deletion of A2A R induces overall cognitive deficits in adult and middle-aged mice. Deficits in cognition are associated to decreases in neurogenesis. A2A R deletion induces changes in synaptic proteins in the PFC and hippocampus.